MTUN technology showcase - Kasran, Abdullah (Penerbit UMP, 2014)
Malaysian Technical University Network (MTUN) comprises of four technology based University. They are: • University Tun Hussein Orin Malaysia (UTHM) • University Technical Malaysia Melaka (UTeM) • University Malaysia Pahang (UMP) • University Malaysia Perlis (UniMAP)